2021
DOI: 10.3168/jds.2020-18478
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: A competitive exclusion study reveals the emergence of Bacillus subtilis as a predominant constitutive microorganism of a whey reverse osmosis membrane biofilm matrix

Abstract: Microbial attachment and colonization on separation membranes lead to biofilm formation. Some isolates within the biofilm microflora acquire greater resistance to the chemical cleaning protocols on prolonged use of membranes. It is thus likely that the constitutive microflora might compete with each other and result in certain species emerging as predominant, especially within older biofilms. To understand the microbial interactions within biofilms, the emergence of predominance was studied in the current inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The study identified distinct bacterial isolates of Exiguobacterium aurantiacum , Acinetobacter radioresistens , Bacillus subtilis , and Bacillus licheniformis ( Table 2 ). Further, it reported the emergence of the predominance of Bacillus subtilis using the co-culturing technique with fifteen combinations of the biofilm isolates [ 48 ].…”
Section: Constitutive Microfloramentioning
confidence: 99%
“…The study identified distinct bacterial isolates of Exiguobacterium aurantiacum , Acinetobacter radioresistens , Bacillus subtilis , and Bacillus licheniformis ( Table 2 ). Further, it reported the emergence of the predominance of Bacillus subtilis using the co-culturing technique with fifteen combinations of the biofilm isolates [ 48 ].…”
Section: Constitutive Microfloramentioning
confidence: 99%